2011
DOI: 10.1063/1.3622302
|View full text |Cite
|
Sign up to set email alerts
|

Formation and decay processes of Ar/He microwave plasma jet at atmospheric gas pressure

Abstract: Dynamic behaviors of gas/plasma mixture generated by microwave discharge jet at atmospheric pressure have been investigated in terms of the effects of working gas dynamics on the discharge characteristics, focusing on the following four points: formation of discharge jet at the ignition phase, growing speed of plasma plume in relation to gas flow rate, acceleration and deceleration of upward movement of plasma plume, and decay process of plasma column at turn-off of microwave power. Four stages are identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 10 publications
2
14
0
2
Order By: Relevance
“…Thence, the bulk plasma density n bulk can be calculated 8:3 Â 10 20 m -3 approximately. It should be mentioned that although this density value is consistent with previous studies reported from the similar lowerpower argon microwave plasma jets driven by continues microwave power in ambient air, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]32 the actual plasma density of the pulsed plasma jet is lower than this value, due to the average power absorbed by the electrons lower largely in pulsed discharge with the same peak power amplitude.…”
Section: Experimental Summarysupporting
confidence: 81%
See 1 more Smart Citation
“…Thence, the bulk plasma density n bulk can be calculated 8:3 Â 10 20 m -3 approximately. It should be mentioned that although this density value is consistent with previous studies reported from the similar lowerpower argon microwave plasma jets driven by continues microwave power in ambient air, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]32 the actual plasma density of the pulsed plasma jet is lower than this value, due to the average power absorbed by the electrons lower largely in pulsed discharge with the same peak power amplitude.…”
Section: Experimental Summarysupporting
confidence: 81%
“…[3][4][5][6][7] Especially for several applications, such as medical instrument sterilization, metal surface nitriding, and high-velocity fuel ignition and combustion, atmospheric microwave plasma devices have shown its potential advantages in industrial applications. [8][9][10][11] There are four types of low-power microwave resonators: coaxial transmission line resonators (CTLR), 3 microstrip line resonators, 4 surfatron launchers, 12 and surface-wave plasma jets, [13][14][15] which are with different characteristics and thereafter are constructed for satisfying different application demands. Generally, these microwave resonators are excited by continuous microwave power supplies.…”
mentioning
confidence: 99%
“…The motivation was the observation of time evolution of a mw helium discharge. The mw discharge imaging was used for argon and helium discharges and observed plasma structure changes [12] and different plasma regimes and modes [7], [13]. This paper concerns temporal evolution of an atmospheric-pressure mw helium plasma and its parameters.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the atmospheric-pressure mw plasma parameters were determined by optical emission spectrum (OES) method in several works. The Boltzmann plot method was used to calculate excitation temperature of argon [6], [7] and helium [8] mw discharges. A 13-mm-diameter helium plasma has been generated by atmospheric-pressure plasma torch that consists of a copper antenna in a quartz tube [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the study of high power microwave (HPM) discharges has attracted a lot of attention in connection with many applications including plasma assisted ignition and flame control, aerodynamic drag reduction at high speeds, sterilization of medical instruments, surface flashover in dielectric windows, design of microwave plasma jets, application in plasma propulsion technology, development of advanced radar systems, removal of nitrogen oxides from exhaust gases, generation of ozone, and purification of the earth atmosphere [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. HPM discharges are characterized by a rapid enhancement of the electron number density in a short period of time of the order of a few nanoseconds.…”
Section: Introductionmentioning
confidence: 99%